“Of Vampire Born”: Interracial Mothering in Black Women’s Speculative Fiction - Löffler, Marie-Luise (Current Objectives of Postgraduate American Studies, 2012)
Focusing on the portrayal of motherhood in black women’s speculative fiction, this essay discusses Jewelle Gomez’s short story “Louisiana 1850“ (1991) and explores how Gomez establishes an egalitarian interracial maternal relationship between a white woman and a slave child. I will demonstrate how the trope of a maternal vampire in particular not only functions in the story to make a mothering relationship plausible, but ultimately challenges and dismantles normative maternal categories, both white and black.